KONTEKS SEJARAH MARITIM INDONESIA DALAM NOVEL ARUS BALIK KAYA PEMOEDYA ANANTA TOER KAJIAN NEW HISTORISM - Kumaidi Kumaidi (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
The literary work has a structure woven from human and kemasyakaratannya. So that literary works were born reflect social conditions surrounding community. In the process, both literary disciplines also offer all kinds of perspectives able to dissect literature today. so also Stepheend Greenblat that offer a new perspective with the approach of New Historism. In a study of New Historism which dissects the history kontteks in Novel Reverse Flow works of Pramoedya Ananta Toer. The data will be obtained in a later novel in the form of a history text that supports the literature was born. Results of studies using qualitative methods diskrptif the formulation of the first to show that, maritime Indonesia has a very vital role in maintaining a region or a state authority. Maritime identical with the sea is a source of life for countries like Indonesia. Sea also has a philosophical meaning, that is by educating the next generation with sea and have insight into the Indonesian marine sea wider than the land.